Automated rainfall simulator for variable rainfall on urban green areas. Issue 26 (2nd September 2019) - Nielsen, Kristoffer T.; Moldrup, Per; Thorndahl, Søren; Nielsen, Jesper E.; Duus, Lene B.; Rasmussen, Søren H.; Uggerby, Mads; Rasmussen, Michael R.
Abstract: Rainfall simulators can enhance our understanding of the hydrologic processes affecting the total runoff to urban drainage systems. This knowledge can be used to improve urban drainage designs. In this study, a rainfall simulator is developed to simulate rainfall on urban green surfaces. The rainfall simulator is controlled by a microcomputer programmed to replicate the temporal variations in rainfall intensity of both historical and synthetic rainfall events with constant rainfall intensity on an area of 1 m 2 . The performance of the rainfall simulator is tested under laboratory conditions with regard to spatial uniformity of the rainfall, the kinetic energy of the raindrops, and the ability to replicate historical and synthetic rainfall events with temporally varying intensity. The rainfall simulator is applied in the field to evaluate its functionality under field conditions and the influence of wind on simulated rainfall. Finally, a field study is carried out on the relationship between runoff, soil volumetric water content, and surface slope. Performance and field tests show that the simulated rainfall has a uniform spatial distribution, whereas the kinetic energy of the raindrops is slightly higher than that of other comparable rainfall simulators. The rainfall simulator performs best in low wind speed conditions. The simulator performs well in replicating historical and synthetic rainfall events by matching both intensity variations and accumulated rainfall depth. The field study shows good correlation between rainfall, runoff, infiltration, soil water content, and surface slope. Abstract : In this study, a physical rainfall simulator was designed to study the relationship between varying rainfall types, runoff, infiltration, soil water content, and surface slope in urban green areas. It was found that the rainfall simulator performed well with great accuracy compared with different types of rainfall and effectively established relationships between soil water content, surface slope, and rainfall–runoff. Generally, the lowest infiltration capacities were found under very dry or fully saturated soil water content conditions.